2020
DOI: 10.1021/acs.macromol.0c00611
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates as Hard Segments for Sustainable Elastomers: Carbohydrates Direct the Self-Assembly and Mechanical Properties of Fully Bio-Based Block Copolymers

Abstract: A series of fully bio-based block copolymers (BCPs) consisting of maltooligosaccharides (maltose, maltotriose, maltotetraose, and maltohexaose; A block) and poly(δ-decanolactone) (PDL; B block), with ABA-, A2BA2-, A3BA3-, A(BA)2-, and A2(BA)2-type architectures, were synthesized to demonstrate the potential of oligosaccharides as novel hard segments for biobased elastomers. To understand the correlation between the BCP molecular structure and material properties, the BCPs were designed to have comparable molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Ring-opening polymerization (ROP) of δ-decanolactone was carried out at 40 °C using diphenyl phosphate (DPP) and 1,4-benzenedimethanol (BDM) as the catalyst and initiator, respectively, according to a procedure previously reported by us, to produce poly(δdecanolactone) diol (HO−PDL−OH) as the central soft segment of the target triblock copolymer. 14 the products confirmed the disappearance of the absorption band at approximately 2100 cm −1 attributable to azido groups (Figures S9−14b), and each SEC elution peak appeared in a higher molecular weight region compared to the azidofunctionalized PDL peak, which suggests that each click reaction proceeded quantitatively (Figure 2). Furthermore, the 1.…”
Section: ■ Results and Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Ring-opening polymerization (ROP) of δ-decanolactone was carried out at 40 °C using diphenyl phosphate (DPP) and 1,4-benzenedimethanol (BDM) as the catalyst and initiator, respectively, according to a procedure previously reported by us, to produce poly(δdecanolactone) diol (HO−PDL−OH) as the central soft segment of the target triblock copolymer. 14 the products confirmed the disappearance of the absorption band at approximately 2100 cm −1 attributable to azido groups (Figures S9−14b), and each SEC elution peak appeared in a higher molecular weight region compared to the azidofunctionalized PDL peak, which suggests that each click reaction proceeded quantitatively (Figure 2). Furthermore, the 1.…”
Section: ■ Results and Discussionsupporting
confidence: 53%
“…Directly combining carbohydrate molecules with synthetic polymers is an effective method for achieving the abovementioned goals; this combination can be achieved mainly through grafting synthetic polymer chains onto polysaccharide main chains, grafting poly/oligosaccharide chains onto synthetic polymer main chains, , and tethering poly/oligosaccharides to synthetic polymers to form block copolymers (BCPs). Among these, the approach that creates carbohydrate-based BCPs is particularly attractive because of the microphase-separation and micelle-forming abilities of these polymers, which are useful when designing elastomers, lithographic materials, electrical materials, and drug-delivery nanocarriers. Carbohydrate-based BCPs remain neglected compared to the other two carbohydrate-containing polymer types because of the difficulties associated with their syntheses. Recent progress in polymer chemistry has witnessed the evolution of strategies for the production of carbohydrate-based BCPs since the pioneering syntheses of carbohydrate-based BCPs were published in 1961. , For example, cellulose- b -polystyrene, dextran- b -polystyrene, and maltoheptaose- b -poly­(ε-caprolactone) have been successfully synthesized by radical polymerization and ring-opening polymerization from the reducing end of the carbohydrate segment. , However, such a synthetic strategy is incompatible with ionic polymerization methods.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this constraint, the enhancement of χ is required, and indeed, numerous research groups have demonstrated microphase-separation from so-called “high χ /low N ” BCPs, resulting in ordered morphologies with d of less than 10 nm. Thus far, silicon-containing [ 3 , 5 , 6 , 7 , 10 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], metal-doped [ 31 , 32 , 33 ], and oligosaccharide-based BCPs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] have been developed. The high χ /low N BCP strategy is now widely accepted as a standard method for obtaining smaller d , although several novel approaches have emerged recently [ 19 , 34 , 35 , 40 , 49 ,…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, silicon-containing [ 3 , 5 , 6 , 7 , 10 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], metal-doped [ 31 , 32 , 33 ], and oligosaccharide-based BCPs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] have been developed. The high χ /low N BCP strategy is now widely accepted as a standard method for obtaining smaller d , although several novel approaches have emerged recently [ 19 , 34 , 35 , 40 , 49 , 50 , 51 , 52 , 53 , ...…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] For example, numerous thermoplastic elastomers with high strength and a tunable modulus have been developed by constructing ABA triblock copolymers wherein B is rubbery and the minority A blocks associate to form hard domains as physical cross-links. [5][6][7] Materials based on this kind of copolymer also have inherent defects in mechanical properties, like creep and hysteresis upon deformation. [8][9][10] Discrete supramolecular interactions such as H-bonding and metal-coordination have been utilized to strengthen the hard domain of copolymers, which represents an effective strategy to modify the mechanical properties of materials.…”
Section: Introductionmentioning
confidence: 99%